Draft Annual Plan (2002-2003) Volume - I Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2002)
Thus, it is decided that, the Department of Agriculture will select progressive farmers in North, Middle and South Andaman including Little Andaman and provide them good quality seeds for multiplication under the supervision of departmental staff and obtain back the resultant seeds on agreed price for distribution to other farmers of the zone annually. This system will ensure seed availability to the farmers at their own areas in cheaper rate and in time.
Andaman and Nicobar Administration, Planning Department
Andaman and Nicobar Administration